Income Inequality: A Journey of 200 Years of Economic Thought - Nurkholisoh Ibnu Aman (The Journal of Indonesia Sustainable Development Planning, 2024)
The phrase "the rich get richer, and the poor get poorer" encapsulates a phenomenon that has long plagued societies worldwide. Most recently, Riddell et al. (2024) showed that, since 2020, the five richest men in the world have doubled their fortunes. At the same time, almost five billion people have seen their wealth fall. It further argued that corporations and its monopoly power are responsible for driving this unrelenting income inequality. This trend is confirmed by Chen et al. (2019) through an investigation into nearly 1 million firms covering 27 countries. Between 2000 - 2015, there has been a notable increase in corporate market power, especially in advanced economies. However, there is no easy solution because inequality is deeply rooted in numerous historical, political, and socioeconomic factors. Therefore, it is imperative to look beyond numbers to understand inequality better. In "Visions of Inequality: From the French Revolution to the End of the Cold War," veteran economist Branko Milanovic takes readers on a journey through the 200-year evolution of economic thought on income inequality. He achieved it by drawing from a diverse source, including original writings, correspondence, and biographical accounts of luminaries in the economics discipline.